PENYELESAIAN SENGKETA MEREK “MARLIN” ANTARA ASTRA HONDA MOTOR (AHM) DAN TREK BICYCLE CORPORATION (STUDI KASUS PUTUSAN KASASI NO. 396 K/PDT.SUS/HKI/MEREK/2024) - Tamaroh, Awik; Borman, Syahrul; Aribawa, Muhammad Yustino; Cornelis, Vieta Imelda (Gapenas Publisher, 2025)
Cross-border trademark disputes are becoming increasingly complex with the rise of trade globalisation and the harmonisation of international legal standards. One notable case is the ‘Marlin’ trademark dispute between Astra Honda Motor (AHM) and Trek Bicycle Corporation, which was decided by the Supreme Court in Case No. 396 K/Pdt.Sus/HKI/Merek/2024. This dispute reflects legal issues regarding trademark registration based on the first-to-file principle, which conflicts with the principle of actual use (use requirement). This research is important to evaluate the implementation of Law No. 20 of 2016 concerning Trademarks and Geographical Indications, as well as to analyse the ratio decidendi of the judges in deciding the case. The main questions raised are how the trademark law provisions were applied in this case and how the judges' considerations formed a precedent in trademark legal protection. The research method used was normative juridical with a case approach. Data were obtained through a literature study of laws and regulations, court decisions, doctrines, and related scientific literature. The analysis was conducted descriptively and analytically by linking the applicable legal norms with the legal facts from the court decisions. The results of the study show that the Commercial Court rejected Trek Bicycle Corporation's lawsuit on formal grounds, while the Supreme Court accepted the lawsuit based on Article 74 of Law No. 20 of 2016, which stipulates that trademarks that have not been used for three consecutive years can be revoked. This decision affirms the principle of actual use as a condition for legal protection of trademarks while strengthening the position of the aggrieved party. The conclusion of this study states that the ratio decidendi of the judges in the ‘Marlin’ case contributed significantly to the development of the doctrine of trademark protection in Indonesia. The implications not only strengthen legal certainty but also encourage healthy business competition and harmonisation with international legal standards. Further research is recommended to explore the effectiveness of trademark cancellation in the context of comparative law across various jurisdictions.